Pengembangan Bahan Ajar Teks Anekdot Di Kelas X SMA Swasta Cerdas Murni Medan - Saidah Sinar Lestari (Journal Innovation In Education, 2024)
This study aims to (1) develop Indonesian teaching materials in the form of teaching modules on anecdotal text material, (2) describe the feasibility of Indonesian teaching materials in the form of teaching modules on anecdotal text material.